2014
DOI: 10.1037/a0037233
|View full text |Cite
|
Sign up to set email alerts
|

How do leader–member exchange quality and differentiation affect performance in teams? An integrated multilevel dual process model.

Abstract: Integrating leader-member exchange (LMX) research with role engagement theory (Kahn, 1990) and role system theory (Katz & Kahn, 1978), we propose a multilevel, dual process model to understand the mechanisms through which LMX quality at the individual level and LMX differentiation at the team level simultaneously affect individual and team performance. With regard to LMX differentiation, we introduce a new configural approach focusing on the pattern of LMX differentiation to complement the traditional approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(160 citation statements)
references
References 89 publications
8
143
1
3
Order By: Relevance
“…The first area for development concerns more research focus on the shape of the LMX distribution. As mentioned earlier, while we identify three main properties of the LMX differentiation process, we noted that there has been virtually no research on LMX variation in relation to LMX shape (for an exception, see Li & Liao, ). While examining, the shape of team distributions has been shown to have importance in relation to other areas in organizational behavior research, such as climate perceptions (e.g., González‐Romá & Hernández, ), work group diversity (e.g., Van Knippenberg & Schippers, ) and for judgments of trust (e.g., De Jong & Dirks, ), such an omission in LMX differentiation research is surprising.…”
Section: Future Research Developmentsmentioning
confidence: 73%
See 2 more Smart Citations
“…The first area for development concerns more research focus on the shape of the LMX distribution. As mentioned earlier, while we identify three main properties of the LMX differentiation process, we noted that there has been virtually no research on LMX variation in relation to LMX shape (for an exception, see Li & Liao, ). While examining, the shape of team distributions has been shown to have importance in relation to other areas in organizational behavior research, such as climate perceptions (e.g., González‐Romá & Hernández, ), work group diversity (e.g., Van Knippenberg & Schippers, ) and for judgments of trust (e.g., De Jong & Dirks, ), such an omission in LMX differentiation research is surprising.…”
Section: Future Research Developmentsmentioning
confidence: 73%
“…Low LMX variation involves equal treatment of followers, which could occur regardless of relative contribution, and thus fulfils the norm of equality and contravenes the norm of equity. Empirical studies examining both cognitive and affective group states (e.g., Chen, He, & Weng, ; Cobb & Lau, ; Li & Liao, ) have reported moderate negative correlations between LMX variation and processes such as group cohesion, group proactivity, coordination, and communication. A particularly noteworthy study is that of Li and Liao () which was longitudinal in design and collected objective outcomes of performance (reported as team profit).…”
Section: Theoretical Approaches and Empirical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have explored the relationship between LMX differentiation and group outcomes, with inconclusive results. Some studies have found that LMX differentiation was related positively to group performance (Naidoo, Scherbaum, Goldstein, & Graen, ), while others reported that LMX differentiation was related negatively to team coordination and, in turn, team performance (Li & Liao, ). Some studies have suggested that the direct effects of LMX differentiation on performance are context‐based.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…An important exception to this approach is that of Li and Liao (2014), who modeled four configurations of LMX differentiation: shared, bimodal, minority and fragmented -each affecting performance through its effects on coordination. Although this study suggests that there are traces of different informal structures in dyadic ties, focusing solely on leader-member relations cannot capture informal social structure with the same breadth as social network approaches.…”
Section: Social Network and Lmx Differentiationmentioning
confidence: 99%